KAJIAN YURIDIS PENANGKAPAN lKAN MENGGUNAKAN BAHAN PELEDAK (STUDI KASUS NELAYAN DI MUARA ANGKE JAKARTA UTARA) - Aulia Atasya Hidayat; Dyah setyorini (Faculty of Law, Universitas Trisakti, 2023)
Catching fish with fishing gear that uses materials or chemicals in marine waters is a practice that can have a negative impact on the safety of marine ecosystems. Additionally, it can lead to damage to coral reefs in Indonesian marine waters. The research is conducted in a normative manner on the fundamental legislative regulations. Furthermore, direct interviews are conducted with fishermen in North Jakarta's Muara Angke. Data processing is carried out qualitatively, and conclusions are drawn using deductive methods. The problem in this research is: What are the policies regarding fishing gear in the Fisheries Law and its implementing regulations, and what are the reasons behind fishing activities carried out by fishermen using explosives (a case study of fishermen in North Jakarta's Muara Angke)? The act of catching fish with explosives falls under the definition of illegal fishing because it contradicts the laws of a country or international regulations. The reason behind fishing with explosives is economic factors because the price of explosives is relatively cheap and easy to find